2010
DOI: 10.1016/j.resuscitation.2009.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of therapeutic hypothermia using convective-immersion surface cooling: Safety, efficacy and outcomes

Abstract: Therapeutic hypothermia has become an accepted part of post-resuscitation care. Efforts to shorten the time from return of spontaneous circulation to target temperature have led to the exploration of different cooling techniques. Convective-immersion uses a continuous shower of 2°C water to rapidly induce hypothermia. The primary purpose of this multi-center trial was to evaluate the feasibility and speed of convective-immersion cooling in the clinical environment. The secondary goal was to examine the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 26 publications
2
36
1
Order By: Relevance
“…The currently available cooling methods have been largely developed in the setting of post-cardiac arrest comatose survivors and are detailed in the following text (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96). Cold infusion.…”
Section: Cooling Techniquesmentioning
confidence: 99%
“…The currently available cooling methods have been largely developed in the setting of post-cardiac arrest comatose survivors and are detailed in the following text (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96). Cold infusion.…”
Section: Cooling Techniquesmentioning
confidence: 99%
“…Moderate-to-mild general hypothermia comprises core temperatures in the range of 30-35°C, which can be induced in the clinic by whole-body cooling pads or immersion in cold water (Howes et al, 2010). A study conducted by Polderman et al (2002) tested the effect of hypothermia treatment on 64 patients with severe head injury.…”
Section: Discussionmentioning
confidence: 99%
“…The automated cold water immersion Thermosuit System (Life Recovery Systems, Kinnelon, NJ) works by the convective-immersion mechanism and circulates ice water from a perforated top-sheet and an under-blanket across the skin surface at a rate of 14 L/min [78]. In a swine study, it has been shown to achieve target temperature of 33°C in 9 minutes.…”
Section: Surface Coolingmentioning
confidence: 99%